Transmission and reflection of a surface wave at a corner of two planes on an isotropic body - PAJEWSKI, W.; SZALEWSKI, M. (Archives of Acoustics, 1983)
This paper reports on an experimental investigation of the diffraction of a Rayleigh wave at a corner of an isotropic solid bounded by two planes forming a dihedral angle with respect to each other. Application of piezoelectric transducers and their appropriate setting on samples permitted the determination of the coefficient of reflection and transmission of Rayleigh waves at a corner and the directional characteristics of transverse waves, with polarisation in a plane perpendicular to the surface of R propagation, radiated at that time by the corner. The results were compared with the results of papers published in the world literature.